Reverse Diaspora Tourism as a New Concept in Tourism: A Study on Turkish-Kazakh Diasporas - Halil İbrahim Karakan; Okan Çolak; Mustafa Mete (SAGE Open)
Reverse diaspora tourism is a form of international tourism in which the diaspora is visited by tourists from the home country, as opposed to diasporas visiting their home countries. This study aims to introduce the concept of reverse diaspora tourism to the literature and to highlight the economic, social, and cultural significance of the travel behavior and spending patterns of “reverse diaspora tourists” by comparing them with traditional diaspora mobility. The case study method, a qualitative research design, was used in this study. In this context, a semi-structured interview form consisting of open-ended questions was developed. Criterion sampling and disproportionate stratified sampling techniques were used to select the sample. In this context, face-to-face and e-mail interviews were conducted with 30 Kazakh diasporas living in Turkey and 30 Turkish diasporas living in Kazakhstan. The data collected from the participants were subjected to thematic analysis using the MAXQDA 2020 analysis program. The study revealed that reverse diaspora tourism is superior to diaspora tourism in terms of economic factors such as number of visitors, overnight stays, and tourism expenditure. In addition, reverse diaspora tourism makes an important social and cultural contribution to destinations. This study is original in that it introduces the concept of reverse diaspora tourism to the literature.